(untitled) - Gubbins, John Harington (London, 1922)
Book is an account of the progress of Japan from pre-feudal days to constitutional government & the position of a great power, with chapters on religion, the complex family system, education, etc
Keywords: Japan,Nhật Bản; History,Lịch sử